Assessment of spectral properties of Apollo 12 landing site - Chemin, Yann H; Crawford, Ian A; Grindrod, Peter; Alexander, Louise (PeerJ Preprints, 2017)
The geology and mineralogy of the Apollo 12 landing site has been the subject of recent studies that this research attempts to complement from a remote sensing point of view using the Moon Mineralogy Mapper (M3) sensor data, onboard the Chandrayaan-1 lunar orbiter. It is a higher spatial-spectral resolution sensor than the Clementine UVVis sensor and gives the opportunity to study the lunar surface with a comparatively more detailed spectral resolution. The M3 signatures are showing a monotonic featureless increment, with very low reflectance, suggesting a mature regolith. The regolith maturity is splitting the landing site in a younger Northwest and older Southeast. The mineral identification using the lunar sample spectra from within the Relab database found some similarity to a basaltic rock/glass mix. The spectrum features of clinopyroxene have been found in the Copernican rays and at the landing site. Lateral mixing increases FeO content away from the central part of the ray. The presence of clinopyroxene in the pigeonite basalt in the stratigraphy of the landing site brings forth some complexity in differentiating the Copernican ray’s clinopyroxene from the local source, as the spectra are twins but for their vertical shift in reflectance, reducing away from the central part of the ray. Spatial variations in mineralogy were not found mostly because of the pixel size compared to the landing site area. The contribution to stratigraphy is limited to the topmost layer which is a clinopyroxene-dominated basalt belonging to the most remote tip of a Copernican ray and its resulting local regolith mix.
Keywords: Apollo12; Moon; hyperspectral; Chandrayaan; M3; clino-pyroxene; Copernicus; Ejecta; Mapping